Perancangan dan Pengembangan Alat Pemotong Tahu yang Ergonomis di UKM Pabrik Tahu Pak Singgi - Seke, Yosef Kasilda Raki; Satoto, Handy Febri (SURYA TEKNIKA, 2024)
The production process at the Pak Singgi Tofu Making UKM, especially for cutting tofu, is carried out with a relatively bent body posture for a long period of time. The process of cutting tofu uses a ruler and knife as cutting tools. The process of cutting tofu takes an average of 10 cutting cycles a day. This makes cutting the tofu take longer and can cause discomfort during the process. To overcome this problem, it is necessary to design and develop ergonomic tofu cutting tools. This research aims to design and create an ergonomic tofu cutting tool to reduce the time needed to cut tofu and provide a more comfortable experience for workers. In this research, an ergonomic tofu cutting tool was designed and manufactured using anthropometric data. The body dimensions used to design the tofu cutting tool are standing waist height (TPB), hand reach (JT), and hand grip diameter (DGT). The average time required to cut tofu with the old tool is 20.1 seconds/box, while the new tool averages 5.4 seconds/box with tool efficiency increasing by 73.34%. The productivity of the old tofu cutting tool was 0.21%, while the new tofu cutting tool was 1% and productivity increased by 0.79%.